Retrofitting Alternatif Refrigeran Ramah Lingkungan R-290 dengan R-134a pada Trainer Unit Instalasi Sistem Refrigerasi - Rizki Muliawan; Muhammad Akmal; Parisya P Rosulindo; Annisa S Kurniasetiawati (P3M Politeknik Negeri Jember, 2026)
R-134a refrigerant has been widely used in industrial and commercial refrigeration systems; however, its high global warming potential (GWP) of up to 1430 has driven the search for more environmentally friendly alternatives. R-290 (propane) is considered a promising candidate due to its zero ozone depletion potential (ODP) and very low GWP of only 3, along with thermodynamic properties that are relatively comparable to those of R-134a. This study aims to evaluate the performance of a refrigeration system retrofitted from R-134a to R-290 using two types of expansion devices, namely a thermostatic expansion valve (TXV) and a capillary tube. The experimental method was conducted by varying the refrigerant charge based on equal mass and maintaining similar evaporator temperature conditions under no-load operation. The results indicate that the system using R-290 is capable of delivering cooling performance comparable to that of R-134a for both types of expansion devices. Furthermore, the use of R-290 results in lower energy consumption, with energy savings ranging from 8% to 9% compared to R-134a. This comparable performance suggests that the thermodynamic properties of R-290 are sufficiently compatible to replace R-134a in the same system without requiring significant modifications to the main components. The observed performance differences are primarily influenced by flow characteristics and the expansion process associated with each type of expansion device. Therefore, R-290 demonstrates strong potential as an environmentally friendly and energy-efficient alternative refrigerant, particularly for retrofit applications in existing refrigeration systems.